Perbandingan Efektivitas antara Ivabradin 5 mg dengan Bisoprolol 5 mg dalam Menjaga Kestabilan Hemodinamik pada Tindakan Laringoskopi Intubasi - Putra, Dany Surya; Syafri Kamsul Arif; Syamsu Hilal Salam; Ramli Ahmad; Andi Salahuddin; Muhammad Rum (Majalah Anestesia & Critical Care, 2023)
Background: Laryngoscopy intubation can cause complications in the form of increased blood pressure and heart rate. This can be detrimental to patients with cardiovascular complications, increased intracranial pressure, and vascular anomalies. Various procedures are performed to stabilize hemodynamic fluctuations during laryngoscopy intubation, one of which is the administration of beta-blocking agents (Bisoprolol). In some studies, the administration of Bisoprolol can cause side effects such as hypotension and bradycardia. One drug considered to maintain hemodynamic stability in laryngoscopy intubation with minimal effects is the administration of Ivabradine, which works by regulating diastolic depolarization. Objective: To compare the effectiveness of Ivabradine 5 mg and Bisoprolol 5 mg in maintaining hemodynamic stability in laryngoscopy intubation. Methods: This double-blind randomized clinical trial was conducted at RSUP Dr. Wahidin Sudirohusodo Makassar in July-August 2022 with ethical qualifications from the Ethics Committee for Biomedical Research in Humans from the Faculty of Medicine, Hasanuddin University. The sample was the entire population that met the inclusion and exclusion criteria. The data were processed using SPSS 25. The analysis used paired T-test, Mann-Whitney, and Wilcoxon with a 95% confidence level (p<0.005). Result: There was a significant decrease in the mean arterial pressure and decrease in heart rate after induction (T2-T0) in the Bisoprolol group (p<0.05). The mean arterial pressure at T1-T0, T3-T0, T3-T2 did not statistically significant. Conclusion: Ivabradine 5 mg was more effective than Bisoprolol 5 mg in maintaining the stability of mean arterial pressure and heart rate in laryngoscopy intubation.